2015
DOI: 10.1007/8904_2015_426
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Findings and Clinical Correlates in Individuals with Infantile-Onset Pompe Disease

Abstract: Pompe disease (OMIM 232300), a glycogen storage disorder caused by deficiency in the lysosomal enzyme acid alpha-glucosidase (EC 3.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 34 publications
3
48
0
Order By: Relevance
“…Follow-up MRI and IQ (patients 1,6,7,9,10) To study the relationship between MRI and IQ, the IQs of the patients assessed with the Griffiths and WISC-III-NL were related to brain MRIs performed at similar ages (time between MRI and IQ assessment <1y, range 0.5-9mo). In patients with involvement of the centrum semiovale and periventricular white matter only, intelligence was normal to mildly delayed (patients' ages 2y 8mo-7y 6mo).…”
Section: Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up MRI and IQ (patients 1,6,7,9,10) To study the relationship between MRI and IQ, the IQs of the patients assessed with the Griffiths and WISC-III-NL were related to brain MRIs performed at similar ages (time between MRI and IQ assessment <1y, range 0.5-9mo). In patients with involvement of the centrum semiovale and periventricular white matter only, intelligence was normal to mildly delayed (patients' ages 2y 8mo-7y 6mo).…”
Section: Intelligencementioning
confidence: 99%
“…However, small amounts of glycogen are also stored in the brain. [6][7][8][9][10][11][12] Therefore, we looked at the potential consequences of glycogen storage in the central nervous system (CNS) using neuropsychological tests and brain magnetic resonance imaging (MRI) from the start of therapy. Previously we found that intelligence ranged from normal to mildly delayed.…”
mentioning
confidence: 99%
“…Therefore, the currently available ERT treatment with rhGAA may not effectively target neural tissue [83] because rhGAA cannot cross the blood-brain barrier. Furthermore, although ERT has significantly improved survival and quality of life of patients with Pompe disease, some patients on ERT still have mild to moderate accumulation of glycogen in the diaphragm [84], intercostal muscles [84], and airway smooth muscle [25,85] and pathology in respiratory control neurons [85]. Therefore, novel therapies need to target both muscle and neuronal pathology in order to treat the respiratory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The diaphragm of Pompe mice lack GAA activity and have accumulation of glycogen that disrupts the structure of the myofibrils and results in muscle weakness [39,40,45,51,52,56,57,86,87]. Similarly, post-mortem studies of patients with both IPD and LOPD reveal glycogen accumulation in the diaphragm [84,[88][89][90]. In some patients, there is severe disruption of the diaphragm myofibrils with degeneration and large vacuoles of glycogen evident on post-mortem studies [89][90][91].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation